2006
DOI: 10.1108/00483480610645821
|View full text |Cite
|
Sign up to set email alerts
|

The changing world of the temporary worker: the potential HR impact of legislation

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…For instance, the UK Labour Force Survey found that agency workers comprised about 16 per cent of all temporary workers, accounting for 1 per cent of the total UK labour force (Forde and Slater 2005). Yet, the Department of Trade and Industry's estimate is closer to 600,000 and others have suggested that the figure is as high as one million (Forde 2001;Biggs, Burchell and Millmore 2006).…”
Section: The Economic Integration Of Migrants and The Globalized Servmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, the UK Labour Force Survey found that agency workers comprised about 16 per cent of all temporary workers, accounting for 1 per cent of the total UK labour force (Forde and Slater 2005). Yet, the Department of Trade and Industry's estimate is closer to 600,000 and others have suggested that the figure is as high as one million (Forde 2001;Biggs, Burchell and Millmore 2006).…”
Section: The Economic Integration Of Migrants and The Globalized Servmentioning
confidence: 94%
“…There has been a rapid growth in the service sector in the UK that has resulted in the creation of low-paid, parttime, non-unionized work (Castells 2000;McDowell 2003). Simultaneously, there has been a significant increase in the utilization of employment and recruitment agencies in the service sector over the last two decades (Biggs, Burchell and Millmore 2006). For instance, the UK Labour Force Survey found that agency workers comprised about 16 per cent of all temporary workers, accounting for 1 per cent of the total UK labour force (Forde and Slater 2005).…”
Section: The Economic Integration Of Migrants and The Globalized Servmentioning
confidence: 99%
“…Indeed, in examining key economic and social indicators, research has shown that the use of temporary workers David Biggs has declined both in the US (Morris & Vekker, 2001) and in the UK (Biggs et al, 2006). In the UK, legislation from the European Parliament has been adopted giving temporary workers greater employment protection.…”
Section: Introductionmentioning
confidence: 98%
“…Legislation could hinder the legitimate functions of the secondary labour market. As temporary workers gain better employment rights, they are likely to become less attractive to employers (Biggs, Burchell and Millmore, 2006). The decline in temporary employment after the implementation of the Flexibility and Security Act in the Netherlands is one example of this effect.…”
Section: The Governmental Dilemma: Worker Rights Versus Economic and mentioning
confidence: 99%